2013
DOI: 10.1152/ajpgi.00425.2012
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase in colorectal cancer

Abstract: Colorectal cancer is the third most prevalent form of cancer worldwide and fourth-leading cause of cancer-related mortality, leading to ϳ600,000 deaths annually, predominantly affecting the developed world. Lysyl oxidase is a secreted, extracellular matrix-modifying enzyme previously suggested to act as a tumor suppressor in colorectal cancer. However, emerging evidence has rapidly implicated lysyl oxidase in promoting metastasis of solid tumors and in particular colorectal cancer at multiple stages, affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…LOX was initially identified as an ECM enzyme that regulated the tensile strength of tissues . Some in vitro studies reported that the LOX gene was a tumor suppressor and its re‐expression could revert H‐Ras‐mediated transformation of NIH 3T3 fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LOX was initially identified as an ECM enzyme that regulated the tensile strength of tissues . Some in vitro studies reported that the LOX gene was a tumor suppressor and its re‐expression could revert H‐Ras‐mediated transformation of NIH 3T3 fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
“…The LOX multigene family comprises five members (LOX, LOXL1, LOXL2, LOXL3, and LOXL4), all of which share a highly conserved homologue sequence within their carboxy terminal region . LOX is an important ECM whose matrix remodeling function has been studied extensively . Elevated LOX expression is reported to be associated with invasion and metastasis in various types of solid tumors, such as breast, melanoma, and head and neck tumors …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cancers [4,7,8]. In contrast, recent publications have demonstrated the overexpression of LOX in many types of solid cancer, including brain [9], head and neck [10], oral and oropharyngeal squamous cell [11], breast [12] and ovarian cancer [13].…”
Section: Research Papermentioning
confidence: 98%
“…One explanation for the seemingly paradoxical role of LOX in cancer is likely the existence of multiple forms and differential localisation of LOX. Increasing evidence indicates that the tumour suppressor activity of LOX lies in the cleaved LOX-PP (18-kDa) which can re-enter the nucleus following extracellular cleavage from the mature enzyme and repress oncogenes such as bcl-2 [4,[16][17][18]. On the contrary, the secreted LOX mature enzyme is typically reported to increase ECM stiffness, activate oncogenic signalling pathways and play a tumour promoting role [19,20].…”
Section: Research Papermentioning
confidence: 99%